2021
DOI: 10.1101/2021.02.15.431277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deletion of Small Ubiquitin-like Modifier-1 Attenuates Behavioral and Anatomical Deficits by Enhancing Functional Autophagic Activities in Huntington Disease

Abstract: Mutant HTT (mHTT) associated with Huntington disease (HD) affects the central nervous system by prominent atrophy in the striatum and promotes psychiatric, cognitive, and choreiform movements, although the exact mechanism remains obscure. Previous studies have shown that SUMO1 (Small Ubiquitin-like Modifier-1) modification of mHTT promotes cellular toxicity, but the in vivo role and functions of SUMO1 in HD pathogenesis are unclear. Here, we report that SUMO1 deletion in Q175DN HD-het knock-in mice (HD mice) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 163 publications
(157 reference statements)
0
1
0
Order By: Relevance
“…Rhes binds to Nix and promotes selective autophagy (mitophagy) [44] . Moreover, we showed that SUMO regulates mTORC1 and autophagy signaling and prevents HD-related deficits in Q175DN-KI model that show enhanced mTORC1 activity [54,73,74] . Previous pharmacological studies with mTORC1 inhibition showed beneficial effects in HD models [54,75] .…”
Section: Multiple Lines Of Evidence Link Rhes In the Autophagy Regulation Rhes Can Activatementioning
confidence: 87%
“…Rhes binds to Nix and promotes selective autophagy (mitophagy) [44] . Moreover, we showed that SUMO regulates mTORC1 and autophagy signaling and prevents HD-related deficits in Q175DN-KI model that show enhanced mTORC1 activity [54,73,74] . Previous pharmacological studies with mTORC1 inhibition showed beneficial effects in HD models [54,75] .…”
Section: Multiple Lines Of Evidence Link Rhes In the Autophagy Regulation Rhes Can Activatementioning
confidence: 87%